YIELD COMPONENTS CHARACTERISTICS OF PROVITA MAIZE VARIETY IN DRYLAND:CORRELATION AND REGRESSION WITH GRAIN YIELD - Yustisia, Yustisia; Amirullah, Johannes (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2019)
The development of high yielding varieties is an alternative to increasing corn productivity in dry land agroecosystems. High-yielding varieties can be selected through the character of the yield components. The assessment was conducted in Talang Taling Village, Gelumbang District, Muara Enim Regency, South Sumatra in May-September 2018. Urea, TSP, KCl, manure and dolomite were given at a dose 350 kg ha-1, 175 kg ha-1, 75 kg ha-1, 2,000 kg ha-1 and 1,000 kg ha-1, respectively. The components of yield observed were ear length, ear diameter, number of rows ear-1, number of kernels row-1, number of kernels ear-1, weight of 1000 grains and weight of kernels ear-1. The correlation between ear length, ear diameter, the number of kernels ear-1 and grain yield was positively significant. Regression analysis showed that there was a highly significant relationship between ear length and grain yield and there was a significant relationship between number of kernels ear-1 and ear diameter and grain yield. Selection highly yield maize variety can be done on the basis of these characters. Characteristics of yield components of ProvitA variety are the length of cobs 13.00-18,90 cm, diameter of cobs 3.90-4.90 cm and number of kernels 204.00-496 grains cobs-1.